Financial Crisis and Current Situation in Global Economy - Ďurkovič, Daniel; Riley, Steven Del; Dvořák, Pavel, 1948-; Vysoká škola ekonomická v Praze. Fakulta managementu (2008)
The goal of the thesis will be to describe the key elements of the economy and its infection by the crisis. It will give an insight on the typology of the crises and today's turmoil in the economic environment. It will try to estimate the impact of the crisis on Slovakia and forecast the development of its national debt
Vedoucí práce: Steven Del Riley
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2009
Rok obhajoby 2009
Keywords: světová ekonomika; finanční krize; veřejný dluh; Slovensko; management [obor bakal. práce]; bakalářské práce; world economics; financial crises; public debts; Slovakia; bachelor's theses